Comparação de métodos de apoio à decisão na seleção de um imóvel - Oliveira, Lucas Santos Menezes e (2008)
This dissertation develops a bibliografical review on Multicriteria method for decision support and Data Envelopment Analysis (DEA). The multicriteria methods for decision aid used were the MACBETH approach and the entropy method applied to a case study related to the real estate sector, in an evaluation and selection of a property to be more precise. Data envelopment analysis was also used in this case study in two differents opportunities: First, the CCR model was used, and then a weight restriction method known as the Assurance Region, type I, also know as "Cone Ratio". The MACBETH approach was used to generate an interval in which each of the criteria could vary. The case study reflects the purchase of a property located in Ilha do Governador district, located in Rio de Janeiro. The alternatives were chosen from a local newspaper, respecting limits previously established for each criterion by the decision-maker, in order to select a few choices from a greater universe of properties located in this district.